Implementation of Sustainable Development Goals (SDGs) and Disaster Risk Reduction (DRR): a Case Study - Peter Davey (Global Medical & Health Communication (GMHC), 2019)
Climate change adaptation and mitigation measures a complicated process and community livelihoods are being seriously impacted. The current local community reality is that climate change and associated disasters are becoming more intense, unpredictable, frequent and costly impacting on rural and urban areas. Disaster Risk Reduction is very important. United Nations General Assembly already set the global policy with the hope that the impact of future disaster events on the community is substantially reduced. Solutions to internal refugee crises start at the local level and require that everyone plays a part: every city, every neighbourhood including farming areas, and every individual can contribute. Leaders must create spaces where everyone can live in safety, become self-reliant, and contribute to and participate in their local community, and not allow people to shift into slum areas after disasters strike. The UNISDR suggests community’s use of the recovery, rehabilitation and reconstruction phases after a disaster to increase the resilience of nations and communities; through integrating disaster risk reduction measures into the restoration of physical infrastructure and societal systems, and into the revitalization of livelihoods, economies, and the environment.